IDENTIFIKASI KEJADIAN OBESITAS PADA LANSIA DI WILAYAH KERJA PUSKESMAS SIDOREJO KIDUL - Kristiawan P. A. Nugroho; R. L. N. K Retno Triandhini; Shara Minantri Haika (MEDIA ILMU KESEHATAN, 2018)
Background: Obesity is one of serious nutritional problems in Indonesia. Based on health profile of Central Java in 2015, Salatiga has the highest percentage of obesity problem counted 71.8% of 561,621 cases. Obesity in elderly are mostly caused by degenerative function of organs which lead to diabetes, hypertension, dyslipidemia, and heart disease. Objective: This study aimed to identify elders’ eating habits, their knowledge of obesity and to identify correlation between the knowledge and obesity. Methods: Observational survey technique by using interview, observation, and questionnaire method was employed to 89 respondents. Correlation among all variables was measured by utilizing Pearson Correlation Coefficient. Results: As many as 10.8% of elderly are obese. Their knowledge regarding Pedoman Gizi Seimbang (PGS) is in sufficient category (69,7%). The respondents had unhealthy eating habit by consuming high carbohydrates and fats which might influence the incidence of obesity. There is no statistical correlation between respondents' knowledge and eating habits (r=-0.37, p>0,05). Conclusion: Even though there is no statistical correlation between respondents’ knowledge and their eating habits, there might be other factors such as age, sex, education, occupation, socio-economic, and family roles that need to be investigated as influencing factors to the obesity incidence in this population. Keywords:Obesity, elderly, knowledge, dietary history, Salatiga